PENDUGAAN KEBUTUHAN AIR TANAMAN DAN NILAI KOEFISIEN TANAMAN (Kc) KEDELAI (Glycine max (L) Merril ) VARIETAS TANGGAMUS DENGAN METODE LYSIMETER - Tia Yuliawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Production of soybean is unbalanced. Increasing number and need of the population is one causes of soybeansscarcity. One factor needs to be considered in soybean cultivation is crop water requirement. This study aims todetermine thewater requirement of soybean bymeasuring evapotranspiration of soybeanlocal varieties directlyby lysimeter (2x3x1)meters. Fieldobservations carried out attwo lysimeters tomeasure crop evapotranspiration(ETc) variety of Tanggamus and one plot planted with grass as standard evapotranspiration (potential). Theresults showed that total soybeancropwater requirement (ETc) forTanggamus is 490.02mmor 6.3mm/hari andthe total per-phase ETc is 5.4; 4.8; 6.7; 7.9 mm/hari. Soybean crop coefficient values (Kc) in the early growthphase, active vegetative, fertilization or seed pod filling, and maturity for the varieties Tanggamus is 0:48; 0.69;0.9; 0.78.